1999
DOI: 10.1021/ol990573k
|View full text |Cite
|
Sign up to set email alerts
|

3-(Diethoxyphosphoryloxy)-1,2,3- benzotriazin-4(3H)-one (DEPBT):  A New Coupling Reagent with Remarkable Resistance to Racemization

Abstract: [formula: see text] The new crystalline phosphate reagent 3-(diethoxyphosphoryloxy)-1,2,3-benzotriazin-4(3H)-one (DEPBT) mediates amide bond formation with a remarkable resistance to racemization. Comparative racemization studies were carried out and DEPBT proved to be superior to typical phosphonium and uronium coupling reagents. DEPBT is easily prepared and is exceedingly stable with a shelf life of months at room temperature. The advantageous properties of DEPBT render it a useful and unique addition to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
146
0
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(160 citation statements)
references
References 13 publications
2
146
0
7
Order By: Relevance
“…However, several studies have reported the presence of just traces of racemization at Gln thioesters [38,39,[42][43][44][45]48] when using protocols similar to those used in our study (PyBOP-coupling conditions); this rules out racemization at the Gln residue of Rev3. On the other hand, the level of racemization in the case of the C-terminal Ser thioester, which we prepared by using BF 3 ·etherate on trichloroacetimidate activated Wang resin, has not been investigated.…”
Section: Chemical Synthesis Of Hiv-1 Revmentioning
confidence: 68%
See 1 more Smart Citation
“…However, several studies have reported the presence of just traces of racemization at Gln thioesters [38,39,[42][43][44][45]48] when using protocols similar to those used in our study (PyBOP-coupling conditions); this rules out racemization at the Gln residue of Rev3. On the other hand, the level of racemization in the case of the C-terminal Ser thioester, which we prepared by using BF 3 ·etherate on trichloroacetimidate activated Wang resin, has not been investigated.…”
Section: Chemical Synthesis Of Hiv-1 Revmentioning
confidence: 68%
“…The Rev3 thioester was prepared in similar yield by anchoring Fmoc-(Glu)-OAll on Rink amide resin (Supporting Information). [42][43][44][45] We then turned our focus to the synthesis of the full length Rev protein by applying the above-described strategy. We first ligated Rev1 to Rev2 under NCL conditions, followed by conversion of the 1,3-thiazolidine-4-carboxo (Thz) to Cys by using methoxylamine, [46] to give Rev2-Rev1 in 35 % isolated yield for the two steps ( Figure 1 A and B).…”
Section: Chemical Synthesis Of Hiv-1 Revmentioning
confidence: 99%
“…This was deprotected with TBAF, and the product was submitted to a Swern oxidation to obtain aldehyde 6 in 94% yield for two steps. Jones oxidation of 6 led to the carboxylic acid intermediate, which was immediately coupled as a crude with aniline in the presence of Goodman's reagent (DEBPT), 24 leading to anilide 7 in 75% yield. Finally, conversion to hydroxamic acid (R/S)-2 was easily achieved by treating methyl ester 7 with hydroxylamine and NaOH in MeOH.…”
mentioning
confidence: 99%
“…To a mixture of 429 mg (1.56 mmol) of glycolate 19, 249 mg (0.510 mmol) of diacid 18, and 360 μL (2.07 mmol) of DIEA in 4.0 mL of THF was added 614 mg (2.05 mmol) of DEPBT 26 . After stirring overnight, the mixture was diluted with 30 mL of ethyl acetate and washed with 10 mL portions of the following: 10% citric acid, water, sat.…”
Section: Chemistrymentioning
confidence: 99%
“…The crude diamine was dissolved in 5 mL of CH 2 Cl 2 , cooled to 0°C, and 222 mg (0.658 mmol) of 9-fluorenylmethyl N-succinimidyl carbonate was added, followed by 90 µL (0.65 mmol) of TEA. After 30 min, the mixture was diluted with 65 mL of ethyl acetate and washed with 20 mL portions of 5% citric acid, 50% brine, and dried over Na 2 26 . After stirring at room temperature for 15 h, the mixture was diluted with 30 mL of ethyl acetate and washed with 10 mL portions of 5% aq.…”
Section: Chemistrymentioning
confidence: 99%